2011
DOI: 10.1002/bjs.7516
|View full text |Cite
|
Sign up to set email alerts
|

Safety of hepatic resection in overweight and obese patients with cirrhosis

Abstract: Hepatic resection can be performed safely in overweight and obese patients with cirrhosis, although morbidity is increased in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 25 publications
3
36
0
1
Order By: Relevance
“…In addition, two studies with large samples earlier indicated that obese and overweight patients did increase workload for surgeons by adding operating time or length of hospital stays[2], [26]. The findings from our study were consistent with some of the previous studies[2], [7], [9], [13], [14], not only in preoperative co-morbidities but also in postoperative outcomes. In general surgery, Dindo[9] investigated a cohort of 6336 patients and found that obese patients had similar postoperative complications except for wound infection.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, two studies with large samples earlier indicated that obese and overweight patients did increase workload for surgeons by adding operating time or length of hospital stays[2], [26]. The findings from our study were consistent with some of the previous studies[2], [7], [9], [13], [14], not only in preoperative co-morbidities but also in postoperative outcomes. In general surgery, Dindo[9] investigated a cohort of 6336 patients and found that obese patients had similar postoperative complications except for wound infection.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, many studies[7][9] have suggested that obesity may have a negative impact on surgical outcomes due to associated co-morbidities, and many studies have assessed the morbidity and mortality in obese patients but the results still remain controversial. Most such studies[7], [10][14] were carried out in western countries and the liver resection was performed in patients with all types of liver diseases. Few studies have focused on Chinese people, in whom the prevalence of obesity and overweight has been lower.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of Cuchetti et al [24], it was shown that liver surgery can be performed safely in overweight and obese patients with HCC. There was only a significantly increase in mild respiratory complications (p = 0.044) in these patients.…”
Section: Prevention Of Phlf – What Can Be Done To Avoid Phlf?mentioning
confidence: 99%
“…Overweight (BMI 25.0–29.9) and obesity (BMI ≥30.0) are significant predictors of adverse postoperative course with an increased morbidity rate after hepatic resection of 31–75 and 42–80%, respectively [41,42]. …”
Section: Pathogenesismentioning
confidence: 99%